Treatment of Traumatic Intrusive luxation injuries of Anterior Permanent Teeth in Pediatric Patient: Case report and Updated Review of Literature - Mohammad Kamran Khan (Journal of Primary Care Dentistry and Oral Health)
Intrusive luxation injuries are one of the severest types of traumatic dental injuries (TDIs) which damage the periodontal ligament, root cementum, pulp, neurovascular bundles, and alveolar bone/socket, and also may unfavorably impact the long-term prognosis of the affected permanent teeth. Although in the existing literature, intrusive luxation injuries of permanent teeth have lower prevalence. However, the literature also reveals that the dental treatment of these types of TDIs is quite challenging due to several associated factors. The published case reports pertaining to dental treatment of such traumatic injuries are considered highly informative and helpful for dentists/clinicians. However, there is a scarcity of published clinical case report articles with comprehensive dental management in this regard. Therefore, this article presents a case report of the dental management of traumatic luxative injuries of permanent anterior teeth with closed apex in a pediatric patient. The International Association of Dental Traumatology guidelines were considered in managing the luxation injuries of permanent teeth and showed success with favorable treatment outcomes in the follow-up. The manuscript has been prepared as per the CARE checklist/guidelines.